EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR FISIKA DI SMA - Purnama, Candra; Suarti, Suarti; Ishak, Suryadi (Universitas Sulawesi Tenggara, 2025)
The Student Team Achievement Division (STAD) cooperative learning model has been widely applied in various disciplines, including physics learning at the high school level. This study aims to analyze the effectiveness of the STAD model in improving physics learning outcomes through literature studies from various relevant studies. The results of the analysis show that the STAD model is able to increase student involvement in learning, strengthen conceptual understanding, and improve learning outcomes significantly compared to conventional methods. The advantage of STAD lies in the structure of group cooperation that encourages active interaction between students, thus creating a more dynamic and enjoyable learning environment. In addition, this model also contributes to improving students' social skills. However, the implementation of STAD requires careful planning and support from teachers so that learning can run effectively. Thus, the STAD model is recommended as one of the effective approaches in physics learning in high school. Informasi Artikel Abstra